Revitalisasi Silek Sunua Dalam Masyarakat Korong Koto Tinggi Kanagarian Gunuang Padang Alai Kabupaten Padang Pariaman - Suci Okta Rahmadani; Indrayuda Indrayuda (SENDRATASIK UNP, 2020)
The background of this research is the loss of one of arts in Korong Koto Tinggi, namely Silek Sunua. This research aims to revitalize Silek Sunua in Korong Koto Tinggi community, Gunuang Padang Alai village, Padang Pariaman regency. The method used was descriptive analysis with a qualitative form. The types of data in this study were primary and secondary data. The main instrument was the researcher itself. The data were collected through literature study, observation, interview, and documentation. The data analysis was conducted by using interpretation technique so that the truth can be obtained. The results of this study are efforts made to revitalize Silek Sunua. The efforts area ctivity excavation and re-activation as well as organization and socializat ionstructuring in Korong Koto Tinggi. Activity excavation and re-activation are done by holding back the Silek Sunua training and having organizational structuring torearrange the structure of the organization. Furthermore, the socialization is to reintroduce Silek Sunua to the community and the younger generation in Korong Koto Tinggi.